Penyetaraan Jabatan Administrasi Ke Dalam Jabatan Fungsional ASN Di Dinas ESDM Provinsi Banten Sebagai Peningkatan Mutu Profesionalisme ASN Berdasarkan Permenpan-RB Nomor 17 Tahun 2021 Tentang Penyetaraan Jabatan Administrasi Ke Dalam Jabatan Fungsional - Sihotang, Elia Fatmawasari; Jazuli, H.E. Rakhmat; Nurikah, Nurikah (Universitas Sultan Ageng Tirtayasa, 2023)
Equalization of administrative positions into functional positions has been carried out by the Banten Province Energy and Mineral Resources Agency. The problem identification is regarding the procedure for equalizing administrative positions into ASN functional positions at the ESDM Office of Banten Province as an increase in the quality of professionalism of the State Civil Apparatus based on Regulation of The Minister of State Apparatus Empowerment and Bureaucratic Reform Number 17 of 2021. As well as the efforts of the Banten Province ESDM Office in improving the quality of ASN professionalism after the procedure for equalizing administrative positions into ASN functional positions at the ESDM Office of Banten Province as an increase in the quality of professionalism of the State Civil Apparatus based on Permenpan-RB Number 17 of 2021. The theories used are Authority Theory and Personnel Management Theory. The research method is empirical juridical. The research specification is descriptive analysis. The data source is primary data supported by secondary data. Data collection techniques are literature study and field study. Data obtained and analyzed descriptively with a qualitative approach method. The results of the study, the Energy and Mineral Resources Agency has implemented the procedure for equalizing administrative positions into functional positions in accordance with Article 14 Permenpan-RB No. 17 of 2021, but the equalized functional officials still carry out the duties and functions of structural officials because there are no further rules regarding reports and responsibilities. Efforts made by the ESDM Service to improve the quality of professionalism of ASN functional officials are attending seminars, socialization and training. The conclusion, based on the research, is that due to the absence of further regulations related to reports and accountability for performance results, the equalized functional officials are still carrying out their old duties and functions so that the original purpose of equalizing positions is not implemented. The suggestion is that BKN is expected to issue policies related to the report system and accountability for performance results.